The Heart and COVID-19: What Cardiologists Need to Know - Costa, Isabela Bispo Santos da Silva (2020)
In face of the pandemic of the novel coronavirus disease 2019 (COVID-19), the management of patients with cardiovascular risk factors and/or disease is challenging. The cardiovascular complications evidenced in patients with COVID-19 derive from several mechanisms, ranging from direct viral injury to complications secondary to the inflammatory and thrombotic responses to the infection. The proper care of patients with COVID-19 requires special attention to the cardiovascular system aimed at better outcomes.